Urbanization Alters the Influence of Weather and an Index of Forest Productivity on Avian Community Richness and Guild Abundance in the Seattle Metropolitan Area - Shryock, Benjamin; Marzluff, John M.; Moskal, L. Monika (Frontiers in Ecology and Evolution, 2017)
Fluctuations in weather and forest productivity influence the abundance and richness of bird populations, however in a rapidly urbanizing landscape the relative importance of each factor may vary. We assessed this possibility in the Seattle, WA, USA region by correlating ten years of bird richness and relative abundance of nine guilds indicative of their tolerance of human development, migration, diet and use of human food subsidies with an annual index of forest productivity (vegetation greenness derived from a 250m resolution Normalized Difference Vegetation Index (NDVI) product from the MODIS satellite) and weather (variation in the Oceanic Niño Index, which estimates the strength of the El Niño-Southern Oscillation, a major driver of local temperature and precipitation). We found that variation in NDVI exerted a strong influence on the richness of the avian community and the abundance of guilds in landscapes undergoing active development, but was less influential in areas of established housing development or forested reserves. Relative to NDVI, weather was much less influential on the abundance of guilds at actively changing sites, and slightly more influential in forest reserves and established developments. Following the warm winter and during the dry summer associated with a strong El Niño, migrants and herbivores declined in changing landscapes, insectivores declined in established developments, and herbivores declined while synanthropic species increased in reserves. These changes may presage the effects of climate change in the Pacific Northwest, which are expected to be similar to El Niño conditions. To buffer these changes in native bird communities, planners, developers, regulators, and home owners should minimize the loss of vegetation during development and attempt to quickly achieve mature landscaping that preferably provides food and shelter for birds.